Digestibility of branched and linear α-gluco-oligosaccharides in vitro and in ileal-cannulated pigs. (January 2020) - Hu, Ying; Heyer, Charlotte M.E.; Wang, Weilan; Zijlstra, Ruurd T.; Gänzle, Michael G.
Graphical abstract: Highlights: Digestion of IMOs was assessed in ileal cannulated swine. Two IMO preparations differing in the proportion of α-(1 → 6) linkages were fed. IMO were partially digested and partially fermented. Structural properties of IMO determine digestibility. Abstract: Isomalto-oligosaccharides (IMOs) may promote health by modulating intestinal microbiota. We hypothesized that the proportion of α–(1 → 6) linkages in IMOs determines their digestibility. Ileal-cannulated pigs were fed diets containing IMO, IMO-DP3 with a greater DP and more α-(1 → 4) linkages, and digestible or resistant maltodextrins. Oligosaccharides were analysed by high-performance anion-exchange chromatography. Compared to IMO, IMO-DP3 contained more panose (18.6 vs. 10.3%) but less isomaltose (7.5 vs. 22.3%) and isomaltotriose (6.1 vs. 12.6%). The apparent ileal digestibility of dry matter were 3% greater for IMO-DP3 and digestible maltodextrin than resistant maltodextrin; the digestibility of IMO was not different from other oligosaccharides. Ileal propionate, isovalerate, and total SCFA was greater for IMO-DP3 and digestible maltodextrin than IMO. In conclusion, IMO was less digestible than IMO-DP3. Structural properties of IMOs are important determinants of their functional properties within the porcine digestive tract.